A study on anatomical variations of celiac trunk and superior mesenteric artery: a computed tomography study - Maskey, Sunima; Karki, Subindra; Mansur, Dil Islam; Shrestha, Sheprala; Shrestha, Pragya; Shrestha, Nilima (Nepal Mediciti Medical Journal, 2025)
BACKGROUND The abdominal aorta and its major anterior branches—the celiac trunk and superior mesenteric artery—exhibit considerable variation in origin and angulation. Understanding these variations is essential for radiologists and surgeons, as they directly influence abdominal interventions, vascular reconstructions, and transplant outcomes. Spiral computed tomography angiography provides a reliable, non-invasive modality for studying such vascular anatomy.METHODS A descriptive cross-sectional study was conducted using 385 contrast-enhanced abdominal CT scans from individuals aged 7–87 years. Origin levels of the celiac trunk and SMA were classified relative to vertebral levels, and the aorta–SMA angle was measured. Data were stratified by age and sex and analyzed using SPSS (v16). Chi-square tests were applied to assess associations between demographic factors and arterial variation.RESULTS The celiac trunk most frequently originated at the T12–L1 level (49.1%), followed by the T12 lower level (22.9%). The SMA most commonly arose from mid-L1 (35.8%) and upper-L1 (30.4%). A clear cranio-caudal shift in SMA origin was observed with advancing age. The mean aorta–SMA angle was 52.68°±20.72°, significantly wider in males (56.64°) than females (49.06°, p < 0.001). Across age groups, the angle showed a non-linear pattern—widest in childhood, narrowing in adulthood, and widening again in older age.CONCLUSIONS This study confirms that the celiac trunk most often arises at T12–L1 and the SMA at L1 levels. The aorta–SMA angle demonstrates both sex-and age-related variation. These findings underscore the importance of population-specific vascular data for safe surgical planning and accurate radiological interpretation.